The IMF or the AMF: Defining the Future of Financing for Investment and Development Projects in Africa - PS Masumbe (Britain International for Academic Research (BIAR-Publisher), 2021)
Since independence the government of many African countries have depended on the International Monetary Fund (IMF) and the World Bank as their main sources of finance for major developmental and investment projects in their respective countries. Accordingly, besides the granting of loans to Low Income Countries (LICs) at zero interest rate, the IMF also assists member countries to resolve their balance of payment challenges as well as granting interest-bearing loans to both member and non-member countries. Similarly, the African Monetary Fund (AMF) which is a prototype of the IMF was created by the African Union (AU) and is not yet operational. Just like the IMF, the AMF is intended to fund major developmental projects in Africa. This article examines the IMF loans conditionality and the award of Special Drawing Rights (SDR) to African Countries as seen during the COVID-19 crisis. It argues that the AMF would not be the African countries’ panacea as far as funding for developmental projects in Africa is concerned. In this regard, the article further examines Agenda 2063 as a future development model for Africa, as well as the various sources of project finance as envisioned in the Frameworks Document of Agenda 2063. It concludes that IMF still has the financial muscle to fund developmental projects and resolved balance of payment problems in Africa despite alternative sources of finance recommended by Agenda 2063.